2022
DOI: 10.14744/semb.2022.32492
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors affecting the development of central lymph node metastasis in papillary thyroid cancer

Abstract: Objectives The most common subtype of thyroid cancer is papillary thyroid cancer (PTC); lymph node metastases are common in this disease. Factors affecting the development of central lymph metastasis of PTC determine the treatment modality and prognosis of the disease. In this study, we aimed to evaluate the clinicopathologic features affecting the development of central lymph node metastasis. Methods The data of a total of 346 PTC patients who were operated between May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Previous studies had found that tumor size was a risk factor for nodal metastasis, as well as ETE and multicentric disease. [ 28 - 30 ] Caliskan et al [ 31 ] found that tumor stage, presence of lymphovascular invasion, and multicentricity were independent risk factors for the development of central lymph node metastasis in adult populations. We did not find a difference in tumor sizes between the patients with and without nodal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had found that tumor size was a risk factor for nodal metastasis, as well as ETE and multicentric disease. [ 28 - 30 ] Caliskan et al [ 31 ] found that tumor stage, presence of lymphovascular invasion, and multicentricity were independent risk factors for the development of central lymph node metastasis in adult populations. We did not find a difference in tumor sizes between the patients with and without nodal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that multicentricity, lymphovascular invasion (LVI), and tumor stage are independent risk factors for determining the possibility of central lymph node metastasis. [ 7 ] We have reported 38% lymph node metastases in central lymph nodes in pT1N0 patients previously. [ 8 ] The impact of CLND on the prognosis of PTC is unclear.…”
mentioning
confidence: 99%